THE IMPACT OF CARE GIVING ON AFRICAN ELDERLY WOMEN CARE GIVERS OF THEIR ADULT CHILDREN WITH AIDS RELATED ILLNESS - Qubuda, Thozamile (Journal of Community and Health Sciences, 2020)
In South Africa, AIDS patients are increasingly cared for at home by women in their traditional role of family caregiver. The number of parents assuming care for their adult children infected with HIV and with AIDS related illness is increasing and this affects parents negatively. The purpose of this phenomenological study was to capture the lived experiences of African elderly women as caregivers in the challenging context of family members who are receiving antiretroviral therapy. The objective of this study is to describe the impact of care giving on elderly African women as caregivers of their adult children with AIDS related illness. The study adopted the qualitative approach using Van Manen's method for hermeneutical phenomenological research to explore the lived experiences of 10 African elderly women who were the primary caregivers for their HIV-positive adult children were investigated. Interviews were audio-taped, transcribed, and subjected to qualitative data analysis. Constant-comparative analysis was done, a process of constantly comparing the data for similarities and differences, guided data analysis, thus capturing all potentially relevant aspects of the data as soon as they were received. Transcription and analysis of the interviews began immediately following the first interview and was preceded by analyzing the transcribed interviews, line by line, highlighting important ideas and themes. Each theme was coded and recoded using Ethnographic computer program. Carers struggled with the physical impact of this disease; there was a clear nexus between the carer's coping capacity and the PLWHA's physical health. As the PLWHA's health declined carers' coping skills were put to the test and new boundaries set.While carers were often 'forced' into silence by the PLWHA, there was a demonstrated desire throughout the research process for these carers to 'debrief' and discuss their past or current care. Of the caregiving, personal care was most difficult and household tasks were most time consuming. Family life, with friends was areas most likely to be affected by caregiving. While it may seem that the carers are coping with care of their children with AIDS, the outer façade is not always an accurate portrayal of the true situation. Health care workers should enquire as to the assistance these carers need from the social and health care services in order to continue to care for their children havingAIDS related illness.